Reducing greenhouse gas emissions in the food sector: Effects of corporate responsibility - Linda Kleemann; Donal Murphy-Bokern (Kiel Institute for the World Economy (IfW), 2014)
The number of firms in the food and agriculture sector that have corporate responsibility (CR) strategies and corresponding reporting is growing rapidly. Many aim, amongst other objectives, to reduce greenhouse gas (GHG) emissions. The question we address here is to what extent such CR measures actually have the potential to significantly affect overall GHG emissions from the agriculture and food sector. We analyse the CR strategies of a sample of 40 firms and from this we provide an assessment of how corporate responsibility addresses GHG emissions. This is achieved in three steps. First, we assess to what extent CR activities are impacting on relevant emission sources. Second, we analyse their current reach and ambition in terms of change envisaged and their contribution to climate protection as a global public good. Third, we consider the drivers behind the development of corporate responsibility to mitigate greenhouse gas emissions in order to estimate the longevity and likely future ambition of these programmes. In addition, we identify firm characteristics that are correlated with strong corporate climate responsibility.
Keywords: 330; greenhouse gas emissions; corporate responsibility; corporate climate responsibility; food value chains